2019
DOI: 10.1002/jor.24242
|View full text |Cite
|
Sign up to set email alerts
|

Protein biomarkers in serum and urine for determining presence or absence of hip dysplasia in a canine model

Abstract: This study compares serum and urine concentrations of relevant protein biomarkers among adult dogs with or without radiographic canine hip dysplasia (CHD). Adult (≥2 years of age), client‐owned dogs (n = 74) radiographically categorized as having at least “good” hips (n = 49) or having “mild,” “moderate,” or “severe” hip dysplasia (n = 25) by the Orthopedic Foundation for Animals (OFA). Urine and serum samples were obtained from each dog at a single time‐point and processed and analyzed for relevant protein bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Based on previous data for application in canine hip dysplasia 13 and DDH, 14 clinically relevant biomarkers with mechanisms related to joint health and disease were selected for testing. To measure dynamics of collagen degradation and synthesis, cross-linked C-telopeptide of type I collagen (CTX-I), and cross-linked C-telopeptide type II collagen (CTX-II), procollagen I C-terminal propeptide (PICP) and procollagen II C-terminal propeptide (PIICP) using commercially available enzyme-linked immunosorbent assays (ELISA) assays (ABclonal; Woburn, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous data for application in canine hip dysplasia 13 and DDH, 14 clinically relevant biomarkers with mechanisms related to joint health and disease were selected for testing. To measure dynamics of collagen degradation and synthesis, cross-linked C-telopeptide of type I collagen (CTX-I), and cross-linked C-telopeptide type II collagen (CTX-II), procollagen I C-terminal propeptide (PICP) and procollagen II C-terminal propeptide (PIICP) using commercially available enzyme-linked immunosorbent assays (ELISA) assays (ABclonal; Woburn, MA).…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] Previous research has identified panels of serum and urine protein biomarkers to discriminate between dogs with healthy hips and those with hip dysplasia, prior to the onset of secondary osteoarthritis. 13 Initial data comparing individuals with DDH, prior to and following diagnosis of hip OA, and from age-matched healthy-hip controls delineated significant differences in mechanistic serum and urine biomarkers between hip-status cohorts. 14 Taken together, these data provide a foundation for development and validation of biomarker panels as a clinically applicable and cost-efficient method for screening, diagnosis, and staging for DDH to avoid misdiagnosis and improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%